2011
DOI: 10.1016/j.gca.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non-metabolizing bacterial cells on the precipitation of U, Pb and Ca phosphates

Abstract: In this study, we test the potential for passive cell wall biomineralization by determining the effects of non-metabolizing bacteria on the precipitation of uranyl, lead, and calcium phosphates from a range of over-saturated conditions. Experiments were performed using Gram-positive Bacillus subtilis and Gram-negative Shewanella oneidensis MR-1. After equilibration, the aqueous phases were sampled and the remaining metal and P concentrations were analyzed using inductively coupled plasmaoptical emission spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 81 publications
6
24
1
Order By: Relevance
“…Precipitates of chernikovite were recently observed by XRD, SEM (or transmission electron microscope), and/or EXAFS (Extended X‐ray adsorption fine structure) in batch studies under uranium and phosphate concentrations similar to those used in the UP system of this study [ Singh et al ., ; Dunham‐Cheatham et al ., ]. In those studies, thermodynamically more favorable solid forms other than chernikovite were not observed as in this study.…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Precipitates of chernikovite were recently observed by XRD, SEM (or transmission electron microscope), and/or EXAFS (Extended X‐ray adsorption fine structure) in batch studies under uranium and phosphate concentrations similar to those used in the UP system of this study [ Singh et al ., ; Dunham‐Cheatham et al ., ]. In those studies, thermodynamically more favorable solid forms other than chernikovite were not observed as in this study.…”
Section: Resultscontrasting
confidence: 53%
“…[] and Dunham‐Cheatham et al . []), and abiotic reactions including adsorption and mineral precipitation [ Morrison and Spangler , ; Naftz et al ., ; Gabriel et al ., ; United States Environmental Protection Agency ( USEPA ), ; Simon and Biermann , ; Wellman et al ., ; Hiemstra et al ., ]. Among these approaches, abiotic precipitation has received considerable attention due to its success in uranium removal from soil and groundwater [ Arey et al ., ; USEPA , ; Fuller et al ., ; Simon et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria are ubiquitous in near-surface environments, and they can adsorb a wide range of metals through interactions with their abundant cell envelope binding sites Murray, 1976, 1980;Plette et al, 1996;Fein et al, 1997), thereby affecting the speciation, distribution and mobility of metals in these systems (Beveridge and Murray, 1976;Templeton et al, 2001;Li and Wong, 2010). Bacterial adsorption of metal also can promote biomineralization reactions (Beveridge et al, 1983;Labrenz et al, 2000;Dunham-Cheatham et al, 2011) and can control metal bioavailability for a range of metabolic processes Hu et al, 2013;Flynn et al, 2014;Sheng and Fein, 2014). Determining the mechanisms responsible for metal adsorption onto bacterial cells, therefore, is critical in order to understand global cycling and transformation of many metals in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to above-mentioned reductive biomineralization of uranium, previous studies have also been primarily focused on the nonreductive biomineralization of U(VI) phosphate by microbes [10,[16][17][18][19][20][21]. However, a comprehensive study on the transformation of uranium is still missing.…”
Section: Introductionmentioning
confidence: 99%